2010
DOI: 10.1017/s1368980010000522
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity score is related to obesity and abdominal adiposity among Iranian female youth

Abstract: Objective: To assess the relationship between diet and disease, consideration of whole-diet indices may be more informative than single-nutrient intake. The present study was conducted to report the relationship among dietary diversity score (DDS), obesity and abdominal adiposity among female university students. Design: Cross-sectional study. Setting: Isfahan, Iran. Subjects: A representative sample of 289 healthy female students aged 18-28 years was selected randomly from Isfahan University of Medical Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
141
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(160 citation statements)
references
References 48 publications
(70 reference statements)
18
141
1
Order By: Relevance
“…Savy et al [32][33][34] reported the association between DDS and BMI or obesity in three publications in the same sample; therefore, the study with the largest sample size was included for analysis. 32 Azadbakht et al 26,28 performed two studies in university students and two in Tehrani adults. 23,24 Because the sample sizes were the same, we chose the study that focused on the DDS-BMI association and provided data in quartiles rather than tertiles to categorize DDS.…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Savy et al [32][33][34] reported the association between DDS and BMI or obesity in three publications in the same sample; therefore, the study with the largest sample size was included for analysis. 32 Azadbakht et al 26,28 performed two studies in university students and two in Tehrani adults. 23,24 Because the sample sizes were the same, we chose the study that focused on the DDS-BMI association and provided data in quartiles rather than tertiles to categorize DDS.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Studies have linked DDS to adverse health such as cardiovascular disease, 23 metabolic syndrome, 24 cancer 25 and obesity; 26,27 however, the association between DDS and obesity have not been fully elucidated. Although some studies have reported inverse associations between DDS and obesity, 21,22,28 others have failed to show this link 29,30 or found positive associations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in adolescents and adults have shown that reduced diet diversity at those ages is associated with obesity. 6,7 The World Health Organization (WHO) developed a set of Infant and Young Child Feeding Indicators in 2008 to monitor population-level complementary feeding practices. 8,9 One of these indicators, minimum dietary diversity (MDD), focuses on the number of food groups given to infants and toddlers in the previous day and is predictive of micronutrient density of the infant's diet.…”
mentioning
confidence: 99%
“…However, the bulk of published studies focus on the implication of DDS on obesity, metabolic disorder, and cardiovascular disease risks in developed countries or nutrition transition contexts (e.g. Azadbakht and Esmaillzadeh, 2011;Azadbakht et al, 2006;Flores et al, 2010;Kant and Graubard, 2005;Li et al, 2011;Roberts et al, 2005). The usefulness of DDS to predict micronutrient health outcomes for adults has only recently been explicitly demonstrated using dietary and laboratory data from the National Health and Nutrition Examination Survey with U.S. adults (Kant and Graubard, 2005).…”
mentioning
confidence: 99%